Human geography for dummies - Tredinnick, Kyle (New Jersey John Wiley & Sons, Inc.., 2024)
Human Geography For Dummies introduces you to the ideas and perspectives encompassed by the field of human geography, and makes a great supplement to human geography courses in high school or college. So what is human geography? It$1 (Bs not about drawing maps all over your body (although you$1 (Bre welcome to do that if you want$1 (Bno judgment). s